Comparative Analysis Of Salam, Samsarah, And Wakalah As Shariah Compliant Models For Dropshipping Transactions - Faza, M. Dzikrullah; Kharis, Aghus Jamaludin; Saidou, Ouedraogo (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study proposes a new comparative fiqh framework to reassess the Sharīʿah legality of dropshipping practices by systematically mapping their business characteristics against the pillars and conditions of three classical contracts—Salam, Samsarah, and Wakālah—within the context of contemporary e-commerce and platform-based trade, which has not yet been comprehensively formulated in previous studies of fiqh al-muʿāmalāt. The research employs a qualitative approach using content analysis and literature review, focusing on classical and contemporary fiqh texts. The analysis applies muqāranah al-madhāhib, synthesized with maqāṣid al-sharīʿah, through the methods of taḥqīq al-manāṭ and qiyās istinbāṭī. The findings indicate that although the dropshipping model is efficient in addressing capital and inventory constraints for micro, small, and medium enterprises (MSMEs), it fundamentally violates the principle of Bayʿ Mā Lā Yamlik (selling what one does not own) and is highly susceptible to gharar concerning ownership (milkiyyah), product specifications, and delivery time. Consequently, Sharīʿah law requires dropshippers to promptly convert their contractual status. This study proposes three Sharīʿah-compliant alternatives: Samsarah, Wakālah or Salam. The study concludes that Wakālah represents the lowest gharar-risk model and offers the most consistent framework for clarifying ownership, risk allocation, and contractual responsibility among the parties involved in the transaction chain.